Tourist Involvement in Creating Social Media Content on Tiktok and Its Impact on Destination Promotion - Sarifiyono, Aggi Panigoro; Kusumawardhani, Aninditha Putri; Rusnendar, Elan; Priyana, Indarta; Pujianto, Anang Bambang; Purnama, Susan; Saberina, Sabilla (Indonesian Scientific Publication, 2024)
The purpose of the study is to identify the factors that motivate tourists in creating content related to tourist destinations on TikTok and analyze their level of involvement in the process. In addition, this study also aims to assess the influence of content produced by tourists on the image and promotion of tourist destinations, as well as evaluate the impact of the content on other tourists' decisions in visiting these destinations. provide recommendations on effective destination promotion strategies through tourist engagement on TikTok. A quantitative method to analyze the relationship between tourist engagement in creating content on TikTok and its impact on the promotion of tourist destinations. The sampling technique was random sampling of 100 respondents. Smart PLS as a tool. The involvement of tourists in creating content on tiktok significantly increases the visibility and attractiveness of tourist destinations. Authentic and personalized content is more effective in influencing other travellers' intentions to visit the destination than formal promotional content. The implications of tourists in creating content on TikTok significantly increase the visibility and attractiveness of tourist destinations. This emphasizes the importance of a marketing strategy that leverages user-generated content to effectively strengthen destination promotion.